Maternal obesity induced metabolic disorders in offspring and myeloid reprogramming by epigenetic regulation - Kweon, Joo Young; Mun, Hyeonji; Choi, Myeong Ryeol; Kim, Hong Seok; Ahn, Yong Joo (Frontiers in Endocrinology, 2024)
Maternal obesity and gestational diabetes are associated with childhood obesity and increased cardiovascular risk. In this review, we will discuss and summarize extensive clinical and experimental studies that metabolically imbalanced environment exposure in early life plays a critical role in influencing later susceptibility to chronic inflammatory diseases and metabolic syndrome. The effect of maternal obesity and metabolic disorders, including gestational diabetes cause Large-for-gestational-age (LGA) children to link future development of adverse health issues such as obesity, atherosclerosis, hypertension, and non-alcoholic fatty liver disease by immune reprogramming to adverse micro-environment. This review also addresses intrauterine environment-driven myeloid reprogramming by epigenetic regulations and the epigenetic markers as an underlying mechanism. This will facilitate future investigations regarding maternal-to-fetal immune regulation and the epigenetic mechanisms of obesity and cardiovascular diseases.